Pemanfaatan Data Mining dalam Penentuan Rekomendasi Mustahik (Penerima Zakat) - Andi Abdul malik Ahmad; Zawiyah Saharuna; Muhammad Fajri Raharjo (Teknik Elektro Politeknik Negeri Padang, 2020)
This study applies data mining in determining recommendations for mustahik. The application is carried out using a classification method with an artificial neural network algorithm where the attributes used are age and type of work of the head of the family, the condition and ownership of the residence, the place of sewage, family monthly income, number of dependents, and diet. Tests are carried out using a combination of values ​​between learning rate, epoch, k-fold, and hidden layer neurons. Based on the test results from the classification process, it is found that the artificial neural network algorithm has the highest accuracy when the number of hidden layer neurons is six, the learning rate is one, the fold is seven, and the number of epochs is 200, which is 92.09%. The test results are then displayed on the Mustahik information system page.